2012
DOI: 10.1587/elex.9.65
|View full text |Cite
|
Sign up to set email alerts
|

Mu-negative, double-negative, and composite right/left handed metamaterials based on dielectric resonators

Abstract: Abstract:In this paper, dielectric-resonator-based metamaterials are reviewed. They are classified mainly into several schemes with explanations of their propagation mechanisms. In addition, recent progress on 1-D, 2-D, and 3-D composite right/left handed metamaterial structures based on one-dielectric-resonator scheme with magnetic dipoles embedded in ε-negative host medium are shown along with their applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Similar homogenization for spherical particles is considered in several papers based on the seminal work of [14][15][16] (see also the review articles [7] and [8] and the references therein). The two lowest Mie resonances for a sphere are given by the scattering coefficients a 1 and b 1 [10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar homogenization for spherical particles is considered in several papers based on the seminal work of [14][15][16] (see also the review articles [7] and [8] and the references therein). The two lowest Mie resonances for a sphere are given by the scattering coefficients a 1 and b 1 [10].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, an alternative approach has been to consider all-dielectric metamaterials based on Mie resonances [6][7][8]. Dielectric materials usually have lower losses, and their dispersion is more moderate in comparison to metals, making the possible applications more broadband.…”
Section: Introductionmentioning
confidence: 99%
“…In the years to follow, extensive research in the field of metamaterials yielded novel metamaterial classes (metamaterials based on dielectric resonators, for example) [7] and configurations [8] in addition to the "classical" ones in the form of metallic split ring and a wire designed by Shelby et al [5] that are shown in (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these issues, the idea of constructing periodic composite media only from non-metallic, dielectric components is being actively explored [15][16][17] . Similar to metallic metamaterials, the goal is to resonantly generate exotic permittivity and permeability properties in a tunable fashion over a certain frequency range.…”
Section: Introductionmentioning
confidence: 99%